Concluding remarks: Fundamentals, applications and future of mechanochemistry. (6th December 2022) - Craig, Stephen L.
Abstract : Mechanochemical response is the result of a complex integration of many factors, but methods for disentangling the various contributions are emerging. Abstract : This paper provides a summary of the Faraday Discussions meeting on "Mechanochemistry: fundamentals, applications, and future" in the context of broad themes whose exploration might contribute to a unified framework of mechanochemical phenomena.